2021
DOI: 10.3389/fonc.2021.620907
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 Triggers Multi-Drug Resistance of Ovarian Cancer via AKT/GSK3β/β-Catenin Signaling

Abstract: Ovarian cancer is the most lethal gynaecologic tumor, with which multi-drug resistance as the major therapeutic hindrance. Heat shock protein 90 (Hsp90) has been involved in cancer malignant behaviors. However, its role and mechanism in multi-drug resistance of ovarian cancer remains poorly understood. Our results demonstrated that Hsp90 was overexpressed in multi-drug resistant ovarian cancer cells. Hsp90 downregulation by shHsp90 or inhibitor BIIB021 increased the sensitivity of multi-drug resistant ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…In a study, the NF-𝜅B was found to be involved in the activation of MDR expression in cancer cells [ 45 ]. Moreover, the inhibition of Hsp90 was documented to contribute to the reversal of cancer MDR [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the NF-𝜅B was found to be involved in the activation of MDR expression in cancer cells [ 45 ]. Moreover, the inhibition of Hsp90 was documented to contribute to the reversal of cancer MDR [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real time PCR was used to evaluate the expression of mRNA according to previous studies 52 . The sequences of primers were:…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for western blot analysis and protein visualization were performed according to our previous studies 52 , 54 . Primary antibodies included anti-Mettl3 (ab195352, Abcam), anti-LDHA (ABN311 - EMD Millipore), and anti-YTHDF1 (ab99080, Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…2 ). For example, apoptosis could be induced in ovarian carcinoma cells when HSP90 is knockout [ 47 ]. But in the model of cerebral ischemia, treating with GA is conductive to the inhibition of apoptosis.…”
Section: Hsp90mentioning
confidence: 99%
“… myeloma [ 108 ] shHSP90 apoptosis Inhibiting the AKT/GSK3β/β-catenin signaling pathway and drug resistance of cancer cells. ovarian carcinoma [ 47 ] Radicicol apoptosis Activating the caspase-8 and bid-dependent pathways and mitochondria-mediated apoptosis. ovarian carcinoma [ 98 ] Curcumin apoptosis Inhibiting the toxic effect of MPP on SH-SY5Y cells; Reducing apoptosis.…”
Section: Hsp90mentioning
confidence: 99%